(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper isa part of my Ph.D. research titled Human Resource Management System inInvestment Perspective of Performance Appraisal of Organisation (A Case Studyon Indian Oil Industry) and includes in thesis as a conclusion chapter-8. Thischapter will draw on those that precede it to answer the research questionsposed in the first chapter of this thesis. It will demonstrate how, through the utilisation of qualitative methodsand statistical analysis, the current study has produced research that has madea valuable contribution firstly, to the decision theory and oil and gasindustry literatures and secondly, to oil industry practitioners. By drawing on the insights gained through theconduct of the literature review, research interviews and data analysis stagesof the current study, the chapter begins by answering each of the threeresearch questions in turn. The mainconclusions of the research are then contextualised in the decision theory andoil industry literatures. Thishighlights how the research has contributed to one of the current debates inthese literatures by providing evidence of a link between the use of decisionanalysis in investment appraisal decision-making and good organisationalperformance. Implications of the studyand recommendations to practitioners follow. The chapter concludes by identifying directions for future research.